Terahertz laminated-structure polarizer with high extinction ratio and transmission power. (16th February 2015) - Kishi, Yudai; Nagai, Masaya; Young, John C.; Takano, Keisuke; Hangyo, Masanori; Suzuki, Takehito
Abstract: A terahertz polarizer consisting of a laminated metal-slit array on a polymer film is presented. Here, the iterative design is efficiently performed with a mode-matching method; the proposed polarizer's characteristics are shown to be superior to those of conventional polarizers. To verify the proposed design, a copper metal-slit array was fabricated on a cyclo-olefin polymer film by sputtering and punching. Measurements confirm a high extinction ratio, below −50 dB from 0.28 to 1.09 THz and below −40 dB from 0.2 to 1.98 THz, with a TM-mode transmission power that averages 76% from 0.2 to 1.95 THz.